Assessment of potential barriers to medicines regulatory harmonization in the Southern African development community (SADC) region - Calder, Amanda (My University, 2016)
Background The World Health Organization (WHO) defines medicines regulation as the “promotion and protection of public health by ensuring the safety, efficacy and quality of drugs, and the appropriateness and accuracy of product information” (1). Medicines regulation is a key function in the realisation of the right to essential medicines. However, a satisfactory level of harmonization of regulatory activities has not been achieved in the Southern African Development Community (SADC) region as yet. Objectives The study evaluated the current status of medicines regulatory harmonization within the SADC region, as well as explored perceived barriers to regulatory harmonization and potential strategies to address these. Methods A cross-sectional exploratory study design with qualitative techniques, as well as an inductive approach was used. In-depth, semi-structured, face-to-face interviews with interviewees from the SADC Secretariat, the African Medicines Harmonization (AMRH) Initiative and the Southern Africa Regional Programme on Access to Medicines and Diagnostics (SARPAM) was used, involving secondary formal qualitative approaches to identify the emergent themes, was utilised initially. A questionnaire was formulated and adapted using secondary data collected from the face-to-face interviews, then piloted. Questionnaires were sent to senior members of all 15 regulatory authorities belonging to SADC, including registrars and deputy registrars. Theoretical and analytical codes were identified from repeated ideas, concepts or elements. Codes were grouped into concepts, and then into categories. Trend analysis was conducted, involving an in-depth analysis of patterns. Results Barriers to regulatory harmonization in the SADC region perceived by participants included i) deficiencies in governance and leadership within the SADC Secretariat, ii) human resource and technical capacity constraints, iii) limited financial resources, iv) lack of political will within SADC governments, v) lack of intra-SADC relationships, vi) risk-benefit analysis differences in assessment of applications and bias according to local population needs, as well as vii) different guidance documents and legal frameworks among member countries. Strategies identified to address these included i) using other harmonization initiatives as models, ii) application format harmonization and African Union (AU) Model Law adoption, iii) redirecting focus of harmonization to information sharing and technical matter rather than complex legislative frameworks, iv) regulator initiatives of harmonization instead of SADC secretariat reliance, v) World Bank Agreement adoption, vi) human resource capacity development and vii) convergence of guidelines instead of complete harmonization of all regulatory requirements. Conclusions The findings in this study suggest that it may be necessary to redirect the focus of harmonization to more readily achievable activities and aim for convergence of guidelines. Regulatory harmonization is possible if barriers to it are addressed.
A Research Report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Master of Science in Medicine (Pharmaceutical Affairs) Johannesburg, 2016
Keywords: World Health Organization; Southern African Development Community (SADC); Health Policy; Africa; Africa, Southern